The Effect of Parental Phubbing on Depression in Chinese Junior High School Students: The Mediating Roles of Basic Psychological Needs Satisfaction and Self-Esteem - Xiao, Xiaofang; Zheng, Xifu (Frontiers in Psychology, 2022)
Objective To reveal the relationship between parental phubbing, basic psychological needs satisfaction, self-esteem, and depression and to explore the impact of parental phubbing on depression. Methods A total of 819 junior high school students responded to the parental phubbing scale, basic psychological needs satisfaction scale, self-esteem scale, and depression scale in combination. Results (1) Parental phubbing was significantly correlated with satisfaction of basic psychological needs, self-esteem, and depression. (2) Parental phubbing can not only be used to directly predict depression in junior middle school students but also has an indirect impact on depression through three pathways: a separate mediating effect on basic psychological needs satisfaction, a separate mediating effect on self-esteem and a chain mediating effect on both. Conclusion Parental phubbing is a risk factor for depression, which can negatively affect the mental health of junior high school students.